Dimensi Sufistik Sulūk Muhammad Kholil Bangkalan - Abdul Munim Cholil (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
This article strives for describing the mystical dimension of sulūk practiced by Muhammad Kholil Bangkalan (known as Shaykhona Kholil) in which his concepts, doctrines, and ethical values of Sufism have been so far secretly unrevealed. All these aspects are covered with his famous and legendary supernatural narratives of his life. The study finds that there has been a similarity of mystical practices of Sufism performed by Shaykhona Kholil and ‘Abd al-Qādir al-Jīlānī. No one has adequate information of Kholil’s mystical life except short diminutive stories he told himself about the process of his khidmah (devotion) to Shaykh ‘Alī Rahbinī. The Sufism practiced by Kholil can be categorized as faṣīh al-ḥāl (the ability to behave in accordance with the very principle of Sufism doctrines), not faṣīh al-lisān wa al-qalam (the ability of presenting speech and writing on Sufims themes). To Kholil, generating capable and well-equipped pupils is more important than giving speech and writing books on Sufism. Therefore, the doctrines of Sufism need to be exemplary nurtured (‘amalī) through actual and practical deeds.